Reliable Adaptive Broadcasting Protocol for VANET - Gupta, Himanshu; Diwakar, Chander (International Journal of Computer Sciences and Engineering, 2025)
Vehicular ad hoc networks (VANET) have turned into an extremely well-known research application to enhance activity wellbeing. The spread of crisis message is viewed as a critical use of VANET. Unicast and multicast method of correspondence used to impart for general messages. To pass on crisis message messages to every one of the vehicles, broadcasting is the reasonable method of correspondence. At the point when a mischance happens, the messages must be conveyed to all the forthcoming vehicles with the goal that the clog and automobile overload can be kept away from. The message can assist the drivers with enabling smooth and safe driving by giving the drivers in different hazard activity conditions. In this paper proposed a reliable adaptive broadcasting protocol for VANET in which uniform and non-uniform segmentations are used to get less latency